ENERGY PERFORMANCE OF RESIDENTIAL BUILDINGS - Filonenko, O. I.; Yurin, O. I.; Kodak, O. A (Academic journal Industrial Machine Building Civil Engineering, 2018)
The problem of the Ukrainian housing stock energy performance is under consideration. Analysis of the outer walling thermal protection condition has been performed for the basic building construction solutions through the example of Poltava. The housing stock is represented by brick, large-block and panel system buildings, erected in the 50–80-th of the last century. The actual values of heat transfer resistance of the outer walls, windows, covers and other building enclosure are 3–5-fold less than the permissible minimum dimension according to the present-day requirements. The article presents recommendations for thermal modernization of the outer walls in accordance with their construction design, attic and basement floors (over the unheated basement), as well as transparent outer structures according to the present-day standard requirements.